Measuring information contents quality of E-Services through mobile devices - Zamzami, Ikhlas; Mahmud, Murni (IIUM Press, 2011)
Mobile devices are important channel for delivering services especially when most users are more dependable on these devices. Information Contents is abundant and accessible by these devices anytime and anywhere. However. there is lack effort that focus on how to ensure the information contents accessed using mobile devices has high quality and satisfy the users. Often time, the same contents which are accessible from the standard size computers are left for the mobile device. The challenges are displaying the most important contents to be seen on the small screen of the mobile device. This book chapter describe interface design and information quality needs and user satisfactions measurement within electronic services. It focuses on the framework to measure relevant qualities and examine relationship among them.